Plasma diagnostic and microstructural study of WCN coatings growth by pulsed vacuum arc discharge. Issue 9 (21st June 2018) - Restrepo‐Parra, Elisabeth; Escobar, Daniel; Ospina, Rogelio; Quintero, Jorge Hernán; Londoño, Ricardo M.
Abstract : In this work, we present a study of the plasma evolution during tungsten carbon nitride (WCN) coatings production using the repetitive pulsed arc technique. For the coatings production, a tungsten carbide (WC) target, and a mixture of argon and nitrogen as the filled gas were used. The study was carried out for discharges generated with one, two, three, and four pulses. The WCN coatings were characterized by X‐ray diffraction (XRD) to identify the phases present in this material. The plasma was experimentally studied by optical emission spectroscopy (OES). A correlation was found between the spectral lines behavior and the material composition evolution. As the number of pulses increased, the intensity of the spectral lines also increased, especially in the case of the atomic lines of nitrogen, NI. The results were analysed to obtain information regarding the reactions in the plasma, as well as the electron temperature and density.